Information technology of situational management profit of the interprise in unstable environment - Осипова, Євгенія Костянтинівна; Лисицький, Василь Лаврентійович (Eastern-European Journal of Enterprise Technologies, 2013)
The article regards the creation of an information technology of situational management of profits of an industrial enterprise in unstable environment. The considered enterprise is characterized by incremental behavior, aimed at minimization of deviations from the conventional behavior inside the enterprise, and in its relations with environment. For effective management of such enterprise we propose the creation of a three-level hierarchical control system, at the middle level of which we recommend to implement the technology of situational control. We suggest the integral characteristics for the analysis of the current situation. To classify the considered problematic situation we realize the output technology based on precedents. A precedent is a description of the problematic situation with the management decision and the result of application of the decision. The visualization of the problematic situation is performed by two-dimensional images. The article presents the information technology of situational management of profit of the enterprise, able to provide a limited set of reliable management decisions. The results can be applied to get the management decision that is the best of those that have been accepted in the management of the enterprise previously